TO DEFINITION OF CONSTRUCTIONS RELIABILITY FROM COMPOSITES AT LOW -CYCLE LOADING - Skachkov , Viktor; Ivanov , Viktor; Pozhuev , Andrej; Rumyantsev , Vladyslav (Scientific Journal "Metallurgy", 2020)
The method of calculation for reliability of unique constructions from composites, which is estimated by exceeding of the limited level of structural damages field, conditioned by distributing microstructure tensions, is developed. Microstructure tensions are determined from the decision of the connected statistical task for deformation and destruction of microunhomogeneous environments. As description of reliability of constructions was used probability of faultless work. One of the specified a preaches of her estimation structuralmechanical that takes into account change of structural parameters of material on conditions of the protracted static or cyclic loading. Destruction of material at the above-mentioned terms is executed highvolume, simultaneously every stage takes place at scale level, comparable with the elements of microstructure which is accompanied by treason of structural elements, both on microscopic and macroscopic levels. For the calculations of the fields of microstresss decide the constrained task of deformation and destruction of heterogeneous bodies on conditions of the cyclic loading At a cyclic ladening process of accumulation of damages condition influence of historical data destruction. Offered approach it was tested during the calculations of the steel thin-walled cylindrical shell (steel of СП- 53) which is on conditions of action of pulsating intrinsic pressure. Dependences of stochastic determined for this shell microscopic tensions and moment functions of distribution of microaccidentfroms the amount of cycles of loading, calculated the mean values of microaccidentfroms and their dispersion depending on the quantity of cycles of loading, and also executed the estimation of probability of faultless work of this construction. It is set that probability of faultless work of constructions considerably goes down on the first cycles of loading and during the next loading diminishes considerably slower, that is predetermined by the phenomenon of adaptability, main reason of which is structural arrangement. Application of the worked out approach can profit at the estimation of reliability of constructions from composites with the obligatory use of generalizations, offered before.